2018
DOI: 10.1109/tpel.2017.2764321
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Model-Predictive-Control-Based Maximum Power Point Tracking for PV Systems: Overview and Evaluation

Abstract: The main objective of this work is to provide an overview and evaluation of discrete model predictive controlbased maximum power point tracking (MPPT) for PV systems. A large number of MPC based MPPT methods have been recently introduced in the literature with very promising performance, however, an in-depth investigation and comparison of these methods have not been carried out yet. Therefore, this paper has set out to provide an in-depth analysis and evaluation of MPC based MPPT methods applied to various co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 98 publications
(52 citation statements)
references
References 54 publications
0
51
0
1
Order By: Relevance
“…Since the performance of FCS-MPC with respect to P&O has been already deeply investigated in [32], and it has been shown that these two methods have equivalent performance, the proposed MPPT is compared to P&O only. Furthermore, P&O is the benchmark algorithm for MPPTs since it is the most classical and adopted in industrial applications.…”
Section: B Experimental Test Benchmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the performance of FCS-MPC with respect to P&O has been already deeply investigated in [32], and it has been shown that these two methods have equivalent performance, the proposed MPPT is compared to P&O only. Furthermore, P&O is the benchmark algorithm for MPPTs since it is the most classical and adopted in industrial applications.…”
Section: B Experimental Test Benchmentioning
confidence: 99%
“…In DO-MPC-MPPT, a digital observer is adopted for the prediction of a PV currents conformable to an assumed PV voltages, where the PV voltages are shifted by a predicted step size. In [32], the efficiency of Discrete-MPCbased MPPT has been deeply studied, considering different weather conditions as well as various power converter topologies, and, as it has been reported, when using FCS-MPC-based MPPT; the resulted MPP tracker will have the same shortcomings as the used reference (in that paper P&O is considered). Regarding DO-MPC-MPPT, a better performance during a changing environmental conditions compared to FCS-MPC-MPPT can be obtained, but tracking the MPP under fast environmental condition changes is still a challenge for DO-MPC as well.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum power generated by the PV system essentially depends on the variations in temperature and solar radiation [52,53]. Thus, MPPT is required.…”
Section: Maximum Power Point Tracking Techniquesmentioning
confidence: 99%
“…where, λ iαβ , λ L1 , and λ b are the weighting factors of the terms of the output current, the inductor L 1 current and the battery current, respectively. To date, there is no exact method for defining the weighting factors of the cost function [15]. PV fed qZSI with battery suffered from the fact that it can not retrieve from the battery a current higher than the PV current, which implies that the converter can not provide the active desired power when the PV power is less than P ref ×50%.…”
Section: ) During Active Statesmentioning
confidence: 99%